Ipratropium is ‘luminally recycled’ by an inter-play between apical uptake and efflux transporters in Calu-3 bronchial epithelial cell layers - Panduga, Vijender; Stocks, Michael J.; Bosquillon, Cynthia (Elsevier, 2017)
The mechanism by which quaternized anticholinergic bronchodilators permeate the airway epithelium remains controversial to date. In order to elucidate the role of drug transporters, ipratropium bidirectional transport as well as accumulation and release studies were performed in layers of the broncho-epithelial cell line Calu-3 grown at an air-liquid interface, in presence or absence of a range of transporter inhibitors. Unexpectedly, a higher transepithelial permeability was observed in the secretory direction, with an apparent efflux ratio >4. Concentration-dependent and inhibitor studies demonstrated the drug intracellular uptake was carrier-mediated. Interestingly, monitoring drug release post cell loading revealed the presence of an efficient efflux system on the apical side of the cell layers. Acting in concert, apical transporters seem to promote the ‘luminal recycling’ of the drug and hence, limit its transcellular transport. The data are in agreement with an apical Organic Cation Transporter (OCT) being involved in this process but also suggest the participation of unknown uptake and efflux transporters sensitive to probenecid. This study suggests the absorption of ipratropium across the pulmonary barrier is primarily governed by paracellular passive diffusion but transporters might play a significant role in controlling the drug local concentrations in the lungs.